Species composition of pathogens of highbush blueberry in the Right-Bank Forest-Steppe of Ukraine - Zlenko, D. S.; Shevchuk, O. V. (Quarantine and plant protection, 2026)
Goal. To identify the fungal communities present in various parts of highbush blueberry plants and to assess the frequency of their isolation. Methods. The study was conducted in the Right-Bank Forest-Steppe of Ukraine in 2022—2025. Plant samples were collected during the growing season and delivered to the laboratory, where they underwent visual inspection and analysis using macroscopic and biological methods. Pathogens were identified based on the cultural and morphological properties of colonies and the morphometric characteristics of sporulation. Results. As a result of the investigations, fungi of 19 genera were isolated from the tissues of infected tall blueberry leaves, 18 genera from branches, and 7 genera from fruits. Fungi Botrytis cinerea and Aureobasidium pullulans, as well as representatives of the genera Alternaria, Cladosporium, Epicoccum, Penicillium and Rhizopus, were isolated from all parts of the plants. Alternaria spp. and Cladosporium spp. were isolated most frequently. Fungi of the genus Epicoccum were more commonly found on leaves and branches (41.8% and 55.5%, respectively). Penicillium spp. were predominantly isolated from leaves. The causative agent of grey rot was most frequently found on fruits, with an isolation frequency of 53.8%, whereas on other parts of the plant it was 23—26%. Rhizopus spp. were isolated from 15.4—19.6% of samples. Fungi of the genera Fusarium, Colletotrichum, Pestalotiopsis, Neopestalotiopsis, Diaporthe were isolated from leaves and branches. Other genera were isolated sporadically. Overall, the mycoflora of highbush blueberry plants, according to our research, comprised 22 genera. Conclusion. The greatest diversity of fungal flora was observed on the leaves of highbush blueberry, and the lowest on the fruit. Throughout the study period, fungi of the genus Alternaria were most frequently isolated from plant tissues. The pathogen Botrytis cinerea was isolated less frequently, mainly from the fruit. Among the isolated fungi, the most harmful phytopathogens of highbush blueberry include Alternaria spp., Fusarium spp., Colletotrichum spp., Pestalotiopsis spp., Neopestalotiopsis spp., Diaporthe spp., as well as the grey mould pathogen Botrytis cinerea. Given the presence of dangerous pathogens in the mycoflora of highbush blueberries that can lead to disease outbreaks and yield losses, continuous phytosanitary monitoring of blueberry plantations throughout the growing season is a key tool for the timely detection of threats and the implementation of appropriate control measures.